2021
DOI: 10.1016/j.cmi.2021.06.036
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 vaccine breakthrough: clinical characteristics of 152 fully vaccinated hospitalized COVID-19 patients in Israel

Abstract: Objectives mRNA COVID-19 vaccines have shown high effectiveness in the prevention of symptomatic COVID-19, hospitalization, severe disease, and death. Nevertheless, a minority of vaccinated individuals might get infected and suffer significant morbidity. Characteristics of vaccine breakthrough infections have not been studied. We sought to portray the population of Israeli patients, who were hospitalized with COVID-19 despite full vaccination. Methods A retrospective mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
270
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(300 citation statements)
references
References 21 publications
27
270
2
1
Order By: Relevance
“…Breakthrough infection in vaccinated asymptomatic subjects, such as those described here, may contribute to the spread of SARS-CoV-2 in the population. Our study is in agreement with several recent reports documenting high viral loads in breakthrough infections in both symptomatic and asymptomatic individuals [7,12,39]. More studies are needed to determine the contribution of breakthrough infections in the spread of SARS-CoV-2 variants of concern.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Breakthrough infection in vaccinated asymptomatic subjects, such as those described here, may contribute to the spread of SARS-CoV-2 in the population. Our study is in agreement with several recent reports documenting high viral loads in breakthrough infections in both symptomatic and asymptomatic individuals [7,12,39]. More studies are needed to determine the contribution of breakthrough infections in the spread of SARS-CoV-2 variants of concern.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with the recent study of Brosh-Nissimov et al that reported the characteristics of breakthrough infections in 152 vaccinated individuals identified from January to April 2021. They reported that 40% of the patients with breakthrough infections were immunocompromised (11% SOT patients), and that co-morbidities including hypertension and diabetes predisposed to severe COVID-19 [7]. Additional studies are needed to determine if SOT patients are vulnerable to specific variants, and if a subset of variants are associated with more severe disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate potential advantages of mucosal immune responses, upcoming studies must mimic the settings more closely that likely contribute to breakthrough infections in vaccinated individuals: age 71 , comorbidities 72,73 , waning immunity, and infection with less neutralization-sensitive variants like B.1.617.2 [12][13][14][15][16][17][18] . However, experimental human challenge studies with a small number of participants might also illuminate this topic similar to challenge studies previously performed in the context of RSV 45,46 or Influenza 74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…Humoral as well as cellular immune responses against the spike (S) surface protein were successfully induced by both types of vaccines [7][8][9][10][11] . However, breakthrough infections of fully vaccinated individuals have been reported and the numbers might increase in the phase of waning immunity [12][13][14][15][16][17][18] . The impact of immune escape and newly emerging virus variants (i.e.…”
Section: Introductionmentioning
confidence: 99%